FAKTOR-FAKTOR YANG MEMPENGARUHI MIGRASI SEUMUR HIDUP DI INDONESIA - Annisatul Husnah; Sri Ulfa Sentosa; Ali Anis (Universitas Negeri Padang, 2019)
This study aims to look at: (1) the influence of education on lifelong migration in Indonesia. (2) Effect of wages on lifetime migration in Indonesia. (3) Effect of employment opportunities on lifelong migration in Indonesia. (4) The effect of marriage on lifelong migration in Indonesia, and (5) The effect of education, wages, employment opportunities and wages together on lifelong migration in Indonesia. This study uses Indonesian Susenas Statistics data from 2005-2016. The analysis technique used is OLS by using the fixed effect model. The results of this study indicate that education has a negative and insignificant effect on lifetime migration. Partially the variables of wages, employment opportunities and marriage have a positive and significant effect on lifetime migration in Indonesia. Taken together the variables of education, wages, employment opportunities and marriage have a significant effect on lifetime migration in Indonesia.